(untitled) (Jalalabad Medical Journal, 2025)
Secondary phimosis is a rare complication following circumcision that results from dense adhesion of redundant foreskin with glans. Multiple issues, such as the performer of the procedure, the method of anaesthesia used, and the patient’s age, are contributory factors for secondary phimosis. Here we reported a case of secondary phimosis presented with acute retention of urine and UTI. Revision circumcision was done as an elective case, and the outcome was satisfactory. Jalalabad Med J 2024; 21 (2); 76-78